Los sistemas de almacenamiento inka de Tambo Viejo - Valdez, Lidio M. (2025)
The Inka State built enormous dispersed warehouses throughout their empire in order to store all types of goods. These facilities were built in clusters, usually atop mountain summits, and seem to suggest that Inka storage systems were always of enormous size. Yet recent archaeological research suggests that smaller scale warehouses, different from those found in the Peruvian highlands, were also erected on the coastlands. This paper examines the cists of Tambo Viejo semisubterranean facilities of varying shape that were also used as storehouses, as follows from the discovery made inside them of items such as maize kernels and coca leaves. This find shows that other forms of storage that probably preceded the development of the State were in place during the Inka expansion on the southern coast of Peru. Just like in the highlands, these forms of storage took advantage of coast’s environmental characteristics in order to attain an efficient preservation of food.